Comportamiento agronómico del cultivo de sorgo (Sorghum bicolor L. Moench), sometido a diferentes niveles de nitrógeno y potasio en la zona de Babahoyo - León Soto, Carlos Alberto (2020)
The present experimental work was carried out on the grounds of the Experimental Farm "San Pablo" of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7 1/2 of the Babahoyo - Montalvo road, Los Ríos Province, with geographic coordinates 01º49` 15 ”south latitude and 79º32` west longitude; with a height of 8 m.s.n.m. The area has a humid tropical climate, with an average annual temperature of 24.7 ° C; annual precipitation 1976 mm; relative humidity 85% and 998.2 hours of heliophany annual average. The graniferous sorghum variety, Hibrido, "Malón" was used as planting material. The proposed treatments consisted of Nitrogen + Phosphorus + Potassium in doses of 250 + 48 + 270 kg / ha; 250 + 48 + 330 kg / ha; 300 + 48 + 270 kg / ha; 300 + 48 + 330 kg / ha; Nitrogen in doses of 250 and 300 kg / ha; Phosphorus in a dose of 48 kg / ha; Potassium in doses of 270 and 330 kg / ha and an absolute witness without application of products. In the present trial, the experimental design “Complete Random Blocks” was used, with ten treatments and three repetitions and the statistical difference between the means of the treatments was determined with the Tukey test with 5% significance. Based on the results obtained, it was determined that the sorghum culture responded favorably to the different levels of nitrogen, potassium in the Babahoyo area; in the evaluation carried out it was observed that the use of Nitrogen + Phosphorus + Potassium in doses of 250 + 48 + 330 kg / ha reached a higher percentage of chlorophyll with 39.2%; plant height, stem diameter, leaf area index, spike length and weight of 1000 grains showed excellent response with the application of Nitrogen + Phosphorus + Potassium in doses of 250 + 48 + 330 kg / ha; The highest grain yield was reported by the use of Nitrogen + Phosphorus + Potassium in doses of 250 + 48 + 330 kg / ha and reached a higher yield with 4010.8 kg / ha and According to the high production costs and depending on the cost of the fertilizer treatments, it was determined that the application of phosphorus in doses of 48 kg / ha reported higher net benefit with $ 341.60.